Onomatopoeia Found in Tintin Comics - Giyatmi Giyatmi; Sihindun Arumi; Ratih Wijayava (English Department of Faculty of Tarbiyah and Teacher Training, 2023)
This research focuses on the use of onomatopoeia in the Tintin comic. This study aims at describing the types of onomatopoeia in Tintin comics. This is descriptive qualitative research. The data of this research are onomatopoeic forms found in Tintin comic. The data sources for this research are 3 Tintin comics, namely Tintin in the Tibet, Tintin and the Alph-Art, and Tintin and Picaros. To collect the data, the writers use documentation (Tintin comic) and content analysis. Data analysis in this study consists of three stages such as data reduction, data display, and conclusion. There are 51 data of onomatopoeia. The writers find there are 3 types of onomatopoeia; phonomime onomatopoeia (29), phenomime onomatopoeia (12), and psychomime onomatopoeia (10).